The Unsolved Riddle of Hanging Rock: Staging the Unknowable - Syofyan, Donny (Jurnal Ceteris Paribus, 2025)
Joan Lindsay's "Picnic at Hanging Rock" is renowned for its enigmatic disappearance and haunting atmosphere. This study examines how Laura Annawyn Shamas's stage adaptation effectively translates this mystery to the theater. By analyzing the play's narrative structure, character development, dialogue, and stage directions, this study reveals how theatrical techniques can convey the unknowable and capture the unsettling ambiance of the source material. The play utilizes a non-linear structure, fragmented dialogue, and evocative lighting and sound design to create an atmosphere of suspense and ambiguity. The characters' emotional responses to the disappearance are heightened, emphasizing the psychological impact of the unknown. Additionally, the play introduces a meta-theatrical element, blurring the lines between reality and fiction, further enhancing the enigmatic nature of the story. The stage adaptation of "Picnic at Hanging Rock" demonstrates theater's unique ability to grapple with ambiguity and the inexplicable, inviting audiences to engage with the story's enduring mystery and contemplate profound questions about human existence and the natural world.